The role of the evaluator in an interactive evaluation of cochlear implantation: shaping power, trust and deliberation. (1st December 2006) - Reuzel, Rob; Grin, John; Akkerman, Tjitske
Interactive evaluation involves a deliberative procedure that has been designed to address poorly structured policy problems in the context of power differences between stakeholders. Basically, it consists of an iterative cycle of interviews with these stakeholders. Power differences are dealt with by anonymising the procedure, the researcher acting as a counsellor exchanging claims, concerns and issues between the stakeholders. However, now the researcher himself or herself becomes a powerful figure. This article describes how a researcher, in an interactive evaluation of pediatric Cochlear Implantation (CI), maintained a balance between constructively using his power to help tackle the policy problem and leaving the ownership of the deliberative process with the stakeholders. To some extent, the procedure was designed to this aim. However, success also critically depends on the researcher's skills in building trust and prudence in applying rules of argumentation.